Teachers' Strategies in Teaching English to Students With Special Needs - Takriyanti, Rizky; Sulistiyo, Urip; Sartika, Delita; Hamdan, Hamdan; Chaniago, Fransisko (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
This research aims to know the teachers’ strategy in teaching English to students with special needs according to their type. The research was designed as a systematic literature review study. The researcher used PRISMA Model for collecting the data. There were 16 research articles that matched the criteria. The data were analyzed through a narrative method. The results of the analysis uncovered various strategies used by teachers. Those are paper braille for reading paper strategies, JAWS App for reading e-text, preview strategy and small group for strategy to obtain the content of instruction, TPR, realia and modeled talk for strategy to obtain the language development, communication games and dictogloss for strategy to encourage active involvement, teacher-mediated, routine-based and specific naturalistic strategies, explained the subject matter, flashcards, pictures, visuals, modifying classroom environment, requested students to always carry the dictionaries, alphabetic signs, patted the students' back to get their attention, repetition strategy, gave examples, song, gave reward, two languages, co-teaching strategy, IEP, differentiated instruction, created oral language comprehension, echolalia, the PECS method to improve communication abilities, direct method, lexical method, SIOP Model, instructional scaffolding, comprehensive support input, posters, real objects, modeling strategies, innovative teaching methods.